DNA Methylation at the Neonatal State and at the Time of Diagnosis: Preliminary Support for an Association with the Estrogen Receptor 1, Gamma-Aminobutyric Acid B Receptor 1, and Myelin Oligodendrocyte Glycoprotein in Female Adolescent Patients with OCD - Nissen, Judith Becker; Hansen, Christine Søholm; Starnawska, Anna; Mattheisen, Manuel; Børglum, Anders Dupont; Buttenschøn, Henriette Nørmølle; Hollegaard, Mads (Frontiers in Psychiatry, 2016)
Obsessive-compulsive disorder (OCD) is a neuropsychiatric disorder. Non-genetic factors and their interaction with genes have attracted increasing attention. Epigenetics is regarded an important interface between environmental signals and activation/repression of genomic responses. Epigenetic mechanisms have not previously been examined in OCD in children and adolescents. The aim of the present study was to examine the DNA methylation profile of selected genes in blood spots from neonates later diagnosed with OCD and in the same children/adolescents at the time of diagnosis compared with age- and sex matched controls. Furthermore, we wanted to characterize the association of the differential methylation profiles with the severity of OCD and treatment outcome. Dried and new blood spot samples were obtained from 21 female children/adolescents with verified OCD and 12 female controls. The differential methylation was analyzed using a linear model and the correlation with the severity of OCD and treatment outcome was analyzed using the Pearson correlation. We evaluated selected Illumina Infinium HumanMethylation450 BeadChip probes within and up to 100,000 bp up- and downstream of 14 genes previously associated with OCD (SLC1A1, SLC25A12, GABBR1, GAD1, DLGAP1, MOG, BDNF, OLIG2, NTRK2 and 3, ESR1, SL6A4, TPH2 and COMT). The study found no significantly differential methylation. However, preliminary support for a difference was found for the gamma-aminobutyric acid (GABA) B receptor 1 (cg10234998, cg17099072) in blood samples at birth and for the estrogen receptor 1 (ESR1) (cg10939667), the myelin oligodendrocyte glycoprotein (MOG) (cg16650906), and the brain-derived neurotrophic factor (BDNF) (cg14080521) in blood samples at the time of diagnosis. Preliminary support for an association was observed between the methylation profiles of GABBR1 and MOG and baseline severity, treatment effect, and responder status; and between the methylation profile of ESR1 and baseline severity. To our knowledge, this is the first study to examine the DNA methylation profiles in OCD. The study points towards possible differences in the methylation profiles and suggests a correlation with the severity of OCD. However, the results warrant further studies in larger sample sets.